The Influence of Remuneration and Motivation on the Performance of State Civil Apparatus is mediated by the Job Satisfaction Variable at the South Cikarang Pratama Tax Service Office - Anwar Kusdiyanto (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
This study aims to: 1) test and analyze the effect of remuneration and motivation on employee job satisfaction 2) test and analyze the effect of remuneration and motivation on employee performance 3) test and analyze the effect of employee job satisfaction on employee performance 4) test and analyze the effect of remuneration and motivation on employee performance mediated by job satisfaction variables. The study was conducted at KPP Pratama Cikarang Selatan with a research sample of 141 respondents. The sampling technique uses saturated sampling technique/census. The data analysis method uses descriptive analysis and path analysis. The results showed that: 1) there is a positive and significant influence of remuneration and motivation on employee job satisfaction 2) there is a positive and significant influence of remuneration and motivation on employee performance 3) there is a positive and significant influence of employee job satisfaction on employee performance 4) there is a positive and significant influence of remuneration and motivation on employee performance mediated by employee job satisfaction variables at KPP Pratama Cikarang Selatan.